Fear of childbirth among pregnant women attending antenatal care in Arba Minch town, southern Ethiopia: a cross-sectional study - Tiruset Gelaw; Teklemariam Gultie Ketema; Kassaw Beyene; Mekdes Kondale Gurara; Gebresilasea Gendisha Ukke (BMC, 2020)
Abstract Background Fear of childbirth is one of the life challenges the women encounter during pregnancy. It is an important source of distress for the women and their families and also increases the odds of obstetric complications during childbirth. The aim of this study was to assess the magnitude of fear of childbirth and associated factors among pregnant women attending antenatal care at public health facilities in Arba Minch town, southern Ethiopia. Methods Institution-based cross-sectional study was carried out among pregnant women who attended antenatal care at public health facilities in Arba Minch from November 1st − 30th 2019. A systematic random sampling technique was employed to include the participants. Data were collected through a face-to-face interview by using a structured and pretested questionnaire. Wijma Delivery Expectancy Questionnaire was used to score fear of childbirth. Epi Data version 3.1 and Statistical Package for the Social Sciences version 25.0 software were used for data management. Descriptive and analytic analyses were done and statistical significance was declared at a p-value < 0.05 and 95% confidence level in multivariable analysis. Results A total of 387 pregnant women have participated in this study. Forty (10.3%) of the pregnant women had a low degree fear, 154(39.8%) had a moderate degree fear, 98(25.3%) had a high degree fear, and 95(24.5%) had severe degree fear of childbirth. Unplanned pregnancy (AOR = 2.30, 95% CI: 1.12, 4.74), current pregnancy-related complications (AOR = 6.24, 95% CI: 2.72, 14.29), and poor social support (AOR = 1.93, 95%CI: 1.01, 3.68) were factors significantly associated with severe degree fear of childbirth. Conclusions Almost three-fourth of the pregnant women in this study area had moderate to severe degree fear of childbirth. Tailoring counseling during antenatal care visits is needed to address those women who are at a high risk of considerable childbirth fear and its health consequences.